Upregulation of FOXO3 in New-Onset Type 1 Diabetes Mellitus - Magdalena Zurawek; Marta Fichna; Piotr Fichna; Maria Czainska; Natalia Rozwadowska (Journal of Immunology Research)
Forkhead box O (FOXO) transcription factors have been implicated in the development and differentiation of the immune cells. FOXO3 plays a crucial role in physiologic and pathologic immune response. FOXO3, cooperatively with FOXO1, control the development and function of Foxp3+ regulatory T cells (Treg). Since the lack of Treg-mediated control has fundamental impact on type 1 diabetes mellitus (T1DM) development, we investigated FOXO3 expression in patients with T1DM. FOXO3 expression was estimated in peripheral blood mononuclear cells (PBMCs) from newly diagnosed T1DM pediatric patients (n=28) and age-matched healthy donors (n=27) by reahavel-time PCR and TaqMan gene expression assays. Expression analysis revealed significant upregulation of FOXO3 in T1DM (P=0.0005). Stratification of the T1DM group according to the presence of initial diabetic ketoacidosis (DKA) did not indicate differences in FOXO3 expression in patients with DKA compared to a mild T1DM onset (P>0.05). In conclusion, overexpression of FOXO3 is correlated with the ongoing islet autoimmune destruction and might suggest a potential role for this gene in the pathogenesis of type 1 diabetes mellitus.